IMPLEMENTASI PENERAPAN INTERNET of THINGS(IoT)PADA MONITORING INFUS MENGGUNAKAN ESP 8266 DAN WEB UNTUK BERBAGI DATA - Dani Sasmoko; Yanuar Arief Wicaksono (Jurnal Ilmiah Informatika, 2017)
The delivery of medical data is of utmost importance to the successful treatment of patients. Efforts have been made in implementing technology both in outpatient services as well as hospital treatments for patients. Internet of things (IoT) is a concept that aims to transmit inherrent data from a physical object through the internet, therefore enabling the receiver on the other end to monitor, process and eventually make decisions based on this data. In this research, the physical object is an intravenous infusion bottle. An ESP 8266 module is connected to a load sensor to measure the volume of the bottle and sends the data via the internet. THe monitoring of the bottle volume can then be done in real time and with precision, without having the nurse manually check the volume or relying on family members to alert the nurse station. The monitoring of the bottle volume has been successfuly done with measurements recorded on a MySQL database and accessible through the web.